A Road Map for School Health Promotion, a Model for Cognitive-Oriented School Health Policy Making and Implementing Policies for Schools - Farinaz Dadaiyn; Jalal Farzami; Amir Pourabbasi; Ata Pourabbasi (Shiraz University of Medical Sciences, 2016)
Background: School health promotion programs implemented in different countries have experienced varying degrees of success. Their success rate depends on various factors such as adaptation with the local charactristics of communities. Objectives: This paper aims to provide an experimental model for school health policy making in a large group of non-governmental schools in Iran. Materials and Methods: To institutionalize school health policies, appropriate organizational structure was established at the headquarters. The road map as "SAMA school health program" was developed in cooperation with the committee of experts and engaging stakeholders. This program was adopted and notified by the health policy council. Results: The main output of this process was compiled in the 36-pages book which has been published and distributed in all of Islamic Azad schools branches. Conclusions: Both structural and the process issues were considered in this template. Engaging policy makers and service providers to make a commitment to the program was the effective intervention for this policy making process. But a low priority of health programs in a notable proportion of school managers, lack of budget and a major obstacle to the implementation of human resources policies remain as the main limitations of our model considered to improve school health promotion.